Bolivia. Logros significativos de 2023 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2024)
The achievements and progress made in the development of the bioeconomy and the conservation of wetlands in Bolivia are highlighted. With regard to the bioeconomy, the Inter-American Institute for Cooperation on Agriculture (IICA) promoted the "Bioeconomy for Family Agriculture" project, promoting capacities in the management of crops, soils and bioinputs, as well as the enactment of municipal laws and the creation of the Bolivian Bioeconomy Network. On the other hand, wetland conservation was addressed through projects financed by the Spanish Agency for International Development Cooperation and Euroclima, with results such as wetland mapping, participatory diagnoses, climate-smart management plans and the formulation of projects to increase the resilience and conservation of these ecosystems. It also highlights the development of institutional and technical capacities in agricultural health, quality and food safety, as well as participation in climate action and financing initiatives. A comprehensive approach to promote sustainable practices, family farming and care for natural resources in Bolivia is evident.